2011
DOI: 10.1007/s11356-011-0602-5
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity of polybrominated diphenyl ethers (PBDEs) for turbot (Psetta maxima) early life stages (ELS)

Abstract: In the perspective of risk assessment, ELS endpoints provide rapid, cost-effective and ecologically relevant information, and links should be sought between these short-term tests and effects of long-term exposures in more realistic scenarios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 38 publications
3
12
0
Order By: Relevance
“…No studies were found in the literature on the effect of PBDE on chitobiase activity. However, our results are consistent with those of Mhadhbi et al (2012) Similarly, Breitholtz and Wollenberger (2003), studying the larval Table 3 Univariate analyses of variance (ANOVA) investigating variations in chitinolytic enzymes activities in Gammarus pulex according to PBDE congener and concentrations and gammarid gender (p-values in bold indicate significant effects of the considered parameter). , respectively).…”
Section: Dose-and Congener-dependent Impact Of Pbdessupporting
confidence: 89%
“…No studies were found in the literature on the effect of PBDE on chitobiase activity. However, our results are consistent with those of Mhadhbi et al (2012) Similarly, Breitholtz and Wollenberger (2003), studying the larval Table 3 Univariate analyses of variance (ANOVA) investigating variations in chitinolytic enzymes activities in Gammarus pulex according to PBDE congener and concentrations and gammarid gender (p-values in bold indicate significant effects of the considered parameter). , respectively).…”
Section: Dose-and Congener-dependent Impact Of Pbdessupporting
confidence: 89%
“…Of course, more detail studies are needed to verify the hypothesis. Previous studies reported that BDE47 was cytotoxic to differentiated cells or stem cells, and toxic to development [10,13], but little is about the mechanism of the BDE47 on the germ cells. Our data suggested that BDE47 induced apoptosis of early leptotene spermatocytes and thus disrupted the spermatogenesis in rat probably due to the deduced expressions of some mitochondrial proteins.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the levels of PBDEs and their residues in the environment and human tissues have increased in recent decades. Of all PBDEs, 2,2 ,4,4 -tetrabromodiphenyl ether (BDE47) was one of the most prevalent congeners in animal and human tissues [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mhadhbi et al (2012) reported on the acute toxicity of PBDEs on embryo-larval He et al (2011) showed that long-term chronic exposure to deca-BDE significantly reduced the gonadosomatic index, sperm density, and sperm motility in zebrafish (Danio rerio) as well as retarded their motor neuron development and locomotion behavior (p < 0.05).…”
Section: Toxicity Of Pbdes In Aquatic Organismsmentioning
confidence: 99%